Improving the performance of microbubble through the modification and optimization of venturi-type generator - Sigit Deddy Purnomo Sidhi; Andreas Pujianto; Akhmad Nurfauzi; Djoko Prasetyo; Basino Basino; Muhammad Alfan Ansori; Egbert Joshua Sirait; Bagas Prakoso (Politeknik Negeri Lhokseumawe, 2024)
Venturi-type generators are recognized as one of the most promising microbubble generators with potential in various fields. However, there is still room for further optimization of their performance to meet the requirements of real applications, such as aeration systems or water treatment applications. This research modified the geometry of a venturi-type generator with specific dimensions: a length of 80 mm, an inside diameter of 26 mm, a throat diameter of 7.2 mm, a convergent nozzle angle of 30°, a divergent diffuser angle of 30°, and an airflow inlet diameter of 6 mm. By varying the water flow rates (i.e., 22 L/min, 26 L/min, and 30 L/min) and air flow rates (i.e., 0.1 L/min, 0.2 L/min, and 0.3 L/min), the study observed the average diameter, size distribution, Standard Oxygen Transfer Rate (SOTR), and Standard Aeration Efficiency (SAE) of the generated microbubbles. This study aims to improve the performance of a microbubble generator, particularly by optimizing the relative size, distribution, and main parameters for real applications. The proposed modification and optimization successfully produced microbubbles with an average diameter of 180-450 μm. Furthermore, the optimal combinations of water and air flow rates (i.e., 30 L/min of water and 0.1 L/min of air) produced approximately 60% of microbubbles with a diameter of no more than 200 μm. These combinations also enable the delivery of a SOTR and SAE values of 0.94 kgO2/h and 1.73 kgO2/kWh, respectively.